A case report of idiopathic iliopsoas hematoma which occurred soon after transfer to the wheelchair after total hip arthroplasty - Okumura, Tomoo (Nagoya J Med Sci, 2017)
A 79-year-old woman was diagnosed with osteoarthritis of the left hip and scheduled for total hip arthroplasty. As two lesions were detected in branches of the coronary arteries, she was treated with catheter treatment. The patient was receiving anticoagulant treatment, which was suspended eight days before the operation; however, heparin was started at 6 days before the operation and was stopped 9 hours before the operation. On the 2nd postoperative day soon after transfer to the wheel chair, she was feeling unwell and was suffering from severe pain in her left buttock and left thigh. Her blood pressure had decreased to 70 mmHg. During abdominal contrast-enhanced CT, a hematoma was detected in the left iliopsoas muscle. Catheter therapy was started by the cardiovascular department and bleeding had stopped spontaneously. The patient was able to walk with a cane and was discharged on the 40th postoperative day. Abbreviations: THA: total hip arthroplasty, CT: computed tomography, JOA score: Japanese Orthopaedic Association hip score, HA: hydroxyapatite, PMMA: polymethyl-methacrylate, APTT: activated partial thromboplastin time